The implementation of English for Specific Purposes (ESP) in the Department of Islamic Banking at STES Manna Wa Salwa Tanah Datar - Muthia Rahman (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2022)
The aim of this study was to examine the current application of English for Specific Purposes (ESP) and its suitability for the students in the Syaria Banking Department at STES Manna Wa Salwa, Tanah Datar. The study employed the total sampling technique as there were 35 students in the Syaria Banking Department. Data were collected through interviews and questionnaires and were analyzed using both quantitative and qualitative methods. The findings indicated that the latest implementation of ESP in this department was appropriate, although there were some areas that needed improvement, particularly in terms of learning materials and time allocation. Additionally, the English course met the needs of the students in the Syaria Banking Department, particularly in terms of improving their vocabulary and speaking skills. The research suggested that lecturers should attend ESP seminars or training programs to enhance their knowledge and skills in providing appropriate teaching and learning materials for students in the Syaria Banking Department. Furthermore, the time allocated for ESP classes should be carefully considered.